Analisis Efisiensi Teknis Pembenihan Ikan Nila di PT Hatchery Nila Kekar Pasuruan - fuad hasan; Dian Retno Asih (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2022)
Along with the increase in fish consumption in Indonesia and the rapid development of freshwater fish farming, it is necessary to guarantee the availability of a supply of seeds that meet the requirements of both quality, quantity and continuity. PT Hatchery Nila Kekar as a producer of tilapia seeds had fluctuations in production caused inefficiency in the use of production inputs. This study aims to identify the factors that influence the production of tilapia hatchery and to analyze the level of technical efficiency. The total sample in the study was 60 pool units taken by census technique. Analysis of factors affecting production and technical efficiency used the Cobb Douglas Stochastic Frontier production function approach. The results of the analysis showed that the production factors that have a significant effect on the amount of production are the variables of ​​​​pond area, number of female broodstock, pellet feed and total weight of broodstock. The technically efficient pools are 34 while 26 pools are not yet efficient.